Identity Disguise: Communication and Resistance Strategies Against Discrimination Against Victims of Sexual Violence - Fitri, Ainal; Husna, Fathayatul (Buana Gender: Jurnal Studi Gender dan Anak, 2024)
Sexual violence is an important issue that must be resolved as quickly and precisely as possible. In general, many cases of sexual violence are experienced by women from various sectors. These victims need help not only to catch the perpetrator and provide counseling, but also need protection in the form of disguised identity. There have been many mental healing efforts provided by various parties to victims of sexual violence, but still few focus on disguising the identities of the victims. In fact, victims also need their identity to be protected as best as possible. This effort has been carried out by one of the religious education institutions in Aceh, namely Dayah Diniyah Darussalam. The Dayah that he leads is used as a safe house for victims of sexual violence and also provides various efforts to restore the mental health of the victims, one of which is by disguising their identity as victims. Departing from this topic, this article examines the communication strategies developed by the Dayah to fight discrimination against victims of sexual violence. This research was studied using a qualitative approach and data was collected by means of in-depth interviews, observation and documentation. This research uses Reflexive Thematic Analysis (RTA) to analyze the found data. The results of the research are that efforts to disguise identity can be used as a communication strategy to protect victims of sexual violence. Keywords: disguise of identity, communication strategy, sexual violence, resistance, discrimination